A serological survey of Bacillus anthracis reveals widespread exposure to the pathogen in free‐range and captive lions in Zimbabwe. Issue 3 (9th October 2020) - Mukarati, Norman L.; Ndumnego, Okechukwu C.; Ochai, Sunday O.; Jauro, Solomon; Loveridge, Andrew; van Heerden, Henriette; Matope, Gift; Caron, Alexandre; Hanyire, Tapiwa G.; de Garine‐Wichatitsky, Michel; Pfukenyi, Davies M.
Abstract: Numerous unknown factors influence anthrax epidemiology in multi‐host systems, especially at wildlife/livestock/human interfaces. Serology tests for anti‐anthrax antibodies in carnivores are useful tools in identifying the presence or absence of Bacillus anthracis in a range. These were employed to ascertain whether the disease pattern followed the recognized high‐ and low‐risk anthrax zonation in Zimbabwe and also to establish whether anthrax was absent from Hwange National Park in which there have been no reported outbreaks. African lions ( Panthera leo) ( n = 114) drawn from free‐range protected areas and captive game parks located in recognized high‐ and low‐risk zones across Zimbabwe were tested for antibodies to anthrax PA antigen using the ELISA immunoassay. A random selection of 27 lion sera samples comprising 17 seropositive and 10 seronegative sera was further tested in the species‐independent toxin neutralization assay (TNA) in order to validate the former as a surveillance tool for anthrax in African lions. Using the ELISA‐PA immunoassay, 21.9% (25/114) of the lions tested positive for antibodies to anthrax. Seropositivity was recorded in all study areas, and there was no significant difference ( p = .852) in seropositivity between lions in high‐ and low‐risk anthrax zones. Also, there was no significant difference (McNemar's chi‐square test = 0.9, p = .343) in the proportion of lions testing positive to anti‐PA anthrax antibodies on ELISA‐PA immunoassay compared with the TNA, with fair agreement between the two tests [kappa (K) statistic = 0.30; 0.08 < K<0.613]. Results of this study indicate that anthrax could be more widespread than 42 currently realized in Zimbabwe, and present in recognized high‐ and low‐risk zones, including 43 where it has not been reported in over 20 years such as Hwange National Park. This is also the 44 first report documenting the presence of anthrax lethal toxin‐neutralizing antibodies in naturally 45 infected carnivores, further confirming exposure to B. anthracis. The research results point to a 46 need for revisiting the currently recognized anthrax risk zones in Zimbabwe. This should be based 47 on improved surveillance of the disease in both wild and domestic animals for better understanding and control of the disease.